Statutory Management Requirements on "Animal Identification and Registration" (Act A7, Act A8): monitoring methods for compliance and related costs in four Italian farms - Speroni, Marisanna; Carè, Sara; Borrelli, Lamberto; Bruni, Antonio; Cabassi, Giovanni; Cappelletti, Maurizio; Degano, Luigi; Claps, Salvatore; Sepe, Lucia; Rufrano, Domenico; Carroni, Antonio Melchiorre; Ruda, Paola; et al. (Italian Journal of Agronomy, 2015)
The European and national laws concerning the identification and registration of livestock are meant to make possible their traceability and facilitate food safety and animal health, especially in case of a disease outbreak; such rules have also become prerequisites that farmers must meet to obtain single farm payments under the common agricultural policy. Failure to comply with these obligations entails the reduction or exclusion from direct payments.Â Act A7, reports the obligations imposed by the EC Regulation 1760/2000 establishing a system for the identification and registration of bovine animals and regarding the labelling of beef and beef products;Â Act A8, report the obligations established by the EC Reg. 21/2004 establishing a system for the identification and registration of sheep and goats. The project MO.NA.CO. monitored the application of rules for identification and registration of cattle, sheep and goats and their costs. The system of identification and registration of dairy cows resulted well organized with a good level of coordination between the involved actors in both farms. The activities necessary for compliance with rules of identification and registration of cattle are distributed throughout the year, but vary from day to day. The average total cost for annual obligations amounted to â‚¬ 533.34 year-1 while the average cost for individual fulfilment in the monitoring period amounted to â‚¬ 4.10. Even in the case of sheep and goats, the monitoring showed a good cooperation between farms and technicians. However, some difficulties were detected, mainly due to the size of the rumen boluses and the limited effectiveness of the ear tags. The operators suggested using smaller rumen boluses and tattoo instead of ear tags; they also suggest to extend the period within which the animals have to be labelled from the current 6 months to 9 months. The cost of compliance amounted to â‚¬ 5.27 head-1 for sheep and â‚¬ 4.90 head-1 for goats.